2007
DOI: 10.1097/coc.0b013e31805c13f0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mentorship on Research Productivity in Oncology

Abstract: Mentorship is valuable to oncologists in enhancing their research experiences. In this selected group, mentorship has effects on current involvement in academic research but not on self-reported publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…In terms of the associations between mentorship and the career outcomes we investigated, unlike evidence from previous literature (e.g., Allen et al, 2018;Illes et al, 2000;Levinson et al, 1991;Riechelmann et al, 2007), we did not find a positive association between mentorship and research productivity or job satisfaction. Rather, we found mentorship to be associated with higher salaries, holding all other factors in the model constant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In terms of the associations between mentorship and the career outcomes we investigated, unlike evidence from previous literature (e.g., Allen et al, 2018;Illes et al, 2000;Levinson et al, 1991;Riechelmann et al, 2007), we did not find a positive association between mentorship and research productivity or job satisfaction. Rather, we found mentorship to be associated with higher salaries, holding all other factors in the model constant.…”
Section: Discussioncontrasting
confidence: 99%
“…Palepu et al (1998) found that medical faculty who had a mentor have higher self-ratings on their research preparation and research skills relative to medical faculty without a mentor. While the majority of studies have suggested positive associations between mentorship and productivity, there are some exceptions (e.g., Riechelmann et al, 2007). Using a survey sample consisting of 339 oncologists and a linear regression approach, Riechelmann et al (2007) found that mentorship is not associated with a higher number of self-reported publications or on becoming a principal investigator.…”
Section: Mentorship and Career Outcomesmentioning
confidence: 99%
“…Furthermore, citation and publication analyses by geographic region are also seen occasionally [28]. As has been seen in other specialties [3,11,[29][30][31], it is a reasonable pursuit to attempt to derive comparative measures of scientific productivity at the institutional and departmental levels as well.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the institutional constructs that define academia have developed to provide a specific infrastructure for scientific efforts [2]. Academic or scientific disciplines such as radiation oncology have a distinct scientific culture that determines, corporately, what paradigms or scientific claims are accepted as valid [3]. Academicians themselves are also often able to describe specific institutional or even departmental subcultures of note.…”
Section: Introductionmentioning
confidence: 99%